Sprayed mortar design to optimize plastering in confined masonry walls (LACCEI, 2024)
Plastering is a procedure that makes it possible to standardize surfaces and fill in the voids to ensure a good finish on masonry walls, as well as increasing their strength and durability. However, this activity generates large amounts of waste related to the loss of material during this construction process. Therefore, it is necessary to implement new technologies to reduce costs and execution times, in addition to obtain the appropriate properties to protect the surface. In the present investigation, the technology of projected mortar for plastering is presented as an innovative alternative to the traditional system. For this reason, twelve sprayed mortar mixtures are designed with w/c ratios of 0.45 and 0.50, Type I and Type V cement contents, accelerating additives and superplasticizer additives mixtures that are tested in the laboratory to propose an optimal mixture according to its properties in the fresh and hardened state. Finally, through unit cost analysis, an estimate of the savings in time and cost that the projected mortar technology presents in comparison with the traditional method for plastering is obtained.